(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This research examines how ethnicity, religion and culture influence human behavior as depicted in Cormac McCarthy’s The Road (2006) and Zadie Smith’s White Teeth (2000). In The Road, McCarthy depicts a post-apocalyptic setting where survival challenges ethical and ethnic limits, whereas White Teeth showcases three culturally diverse families in London, the Joneses (mixed English and Jamaican), the Iqbals (from Bangladesh), and the Chalfens (Caucasian English). These stories emphasize how both ethnicity and religion shape choices and identity, particularly when characters function outside of legal frameworks. The research aims to find out if ethnicity, religion or culture has a more significant influence on human behavior, examined from a postcolonial perspective. It centers on themes of identity, ethnicity, multiculturalism, ethics, and belief to examine how these elements shape both individual and group behavior. The study indicates that deeply ingrained ethnicity and religious beliefs have a substantial impact on behavior. Nevertheless, when faith is weak or not firmly established, cultural standards often take precedence as the main direction. Therefore, the study indicates that without firm religious beliefs, culture plays a significant role in shaping a person’s decisions and moral limits.